2022
DOI: 10.3390/plants11101370
|View full text |Cite
|
Sign up to set email alerts
|

Plant Species Complementarity in Low-Fertility Degraded Soil

Abstract: The aim of this study was to investigate the compatibility of plants with contrasting root systems, in terms of procurement of limiting soil nutrients. Paired combinations of species of proteas and grasses were grown in a pot experiment using soil from a site with impoverished vegetation and degraded soil. The soil contained sufficient N but was low to deficient in P, Mn, S, Fe, and B. The uptake of chemical elements into the foliage differed significantly according to whether the plants were growing as single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…For the other species, C. cheesemanii and P. cita, there is no record of studies using organic amendments with these plants, and there is a lack of knowledge about their nutrient requirements. Their non-significant response to the amendments may be due to the plants being naturally adapted to low fertility environments [69,70]. Other indigenous NZ plants that did not respond to biosolids in previous studies [39] include Phormium cookianum Ozothamnus leptophyllus, Coprosma acerosa, and V. salicifolia, which had no significant biomass increase when biosolids were incorporated into two low-fertility soils, an Orthic brown soil and sand [39].…”
Section: Discussionmentioning
confidence: 96%
“…For the other species, C. cheesemanii and P. cita, there is no record of studies using organic amendments with these plants, and there is a lack of knowledge about their nutrient requirements. Their non-significant response to the amendments may be due to the plants being naturally adapted to low fertility environments [69,70]. Other indigenous NZ plants that did not respond to biosolids in previous studies [39] include Phormium cookianum Ozothamnus leptophyllus, Coprosma acerosa, and V. salicifolia, which had no significant biomass increase when biosolids were incorporated into two low-fertility soils, an Orthic brown soil and sand [39].…”
Section: Discussionmentioning
confidence: 96%
“…Studies have shown that nutrients may be a major limiting factor for species coexistence and plant productivity in polluted environments [86,103]. However, plant assemblages can increase the ability of each species to obtain key elements from the soil nutrient pool [104]. Thus, when ecological niche overlap among plants is high (e.g., Zea mays and Suaeda saltbush I [16], Solanum melongena and Sedum alfredii [52]), it will increase nutrient competition among species and weaken the facilitative effect of plant combination cropping systems.…”
Section: Factors Influencing the Restoration Of Multi-plant Symbiotic...mentioning
confidence: 99%